Tata Kelola Galangan Kapal Kayu di Desa Bahari I, Kecamatan Sampolawa Kabupaten Buton Selatan - Samaluddin Samaluddin; Azhar Aras Mubarak; Rahmawati Djunuda (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The wooden shipyard in Bahari Village is a privately-owned facility that conducts maintenance, repair, and construction of new wooden ships. The vessels serviced at this shipyard range from 10 GT to 25 GT and are made from wood. The purpose of this research is to evaluate the management of the wooden shipyard in Bahari I Village, Sampolawa District, South Buton Regency. The methodology used is a survey method, and the data is analyzed using fishbone analysis followed by a descriptive approach. The results of this study indicate that the construction and repair processes of wooden ships in Bahari I Village are not efficient due to facilities that do not meet standards, with only 22% of the necessary conditions being fulfilled. The management of this wooden shipyard is still far from adequate because several aspects remain uncontrolled, such as the shipbuilding process not meeting expected targets, delays in the availability and delivery of raw materials, and the use of very basic tools and outdated technology.